2015
DOI: 10.1002/anie.201506881
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Chiral Pyrazoles: A 1,3‐Dipolar Cycloaddition/[1,5] Sigmatropic Rearrangement with Stereoretentive Migration of a Stereogenic Group

Abstract: Abstract:The reactions between terminal alkynes and -chiral tosylhydrazones lead to the obtention of chiral pyrazoles with a stereogenic group directly attached at a nitrogen atom, through cascade reactions that include decomposition of the hydrazone into a diazocompound, 1,3-dipolar cycloaddition of the diazo compound with the alkyne and 1,5-sigmatropic rearrangement with migration of the stereogenic group. This strategy have been succesfully applied to the synthesis of structurally diverse chiral pyrazoles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…In recent years,s everal methods for the preparation of substituted pyrazoles have been reported such as addition-cyclization, [2+ +2+ +1] annulation or ringopening/cyclization. [2] However,t here is still an eed for simple and effectivemethods for the preparation of 4-arylpyrazoles.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years,s everal methods for the preparation of substituted pyrazoles have been reported such as addition-cyclization, [2+ +2+ +1] annulation or ringopening/cyclization. [2] However,t here is still an eed for simple and effectivemethods for the preparation of 4-arylpyrazoles.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, however this reaction was carried out in toluene at 145 °C in a sealed tube. Recently, Valdés et al reported the synthesis of chiral pyrazoles through the [3+2]‐dipolar cycloaddition of α‐chiral tosylhydrazones with alkynes (Scheme , B) . Interestingly, they observed that the initial cycloadduct underwent [1,5]‐sigmatropic rearrangement with migration of the alkyl group.…”
Section: Resultsmentioning
confidence: 99%
“…[26] The authors rationalised the transformation through the formation of the enol intermediate which (Scheme 11, B). [27] Interestingly, they observed that the initial cycloadduct underwent [1,5]-sigmatropic rearrangement with migration of the alkyl group. Significantly in their study, they observed that the [1,5]-sigmatropic rearrangement, which has two regioisomeric outcomes, preferentially, but not exclusively, migrates to nitrogen rather than the C(4) carbon.…”
Section: [3+2]-dipolar Cycloadditions Of α-Sulfonyl-chloroacrylamidesmentioning
confidence: 99%
“…For these purposes, versatile strategic approaches for the synthesis of aromatic and benzylic N‐substituted pyrazoles have been reported to proceed regioselectively . However, to date, only very limited examples have been documented accessing enantioenriched benzylic N‐substituted pyrazoles in a straightforward, regioselective fashion . The preparation of such chiral pyrazoles either requires multiple steps or is accompanied by the generation of stochiometric amounts of waste as well as strong limitations regarding the substrate variability…”
Section: Methodsmentioning
confidence: 99%